Checkpoint immunotherapy is associated with preferential activation of tumor antigen–specific CD4+ T cells in MDS - Elizabeth A. Griffiths; Pragya Srivastava; Eduardo Cortes Gomez; Junko Matsuzaki; Kunle Odunsi; Laura W. Dillon; Devdeep Mukherjee; Christopher S. Hourigan; Jacqueline Peng; Shovik Bandyopadhyay; Kai Tan; Kristopher M. Attwood; et al. (Blood Neoplasia)
Abstract: A growing body of literature suggests that the efficacy of DNA hypomethylating agents are mediated via activation of antitumor immune mechanisms. Based upon this hypothesis, early phase trials combining immune checkpoint inhibitors (ICIs) with azacitidine in patients with myelodysplastic syndrome (MDS)/acute myeloid leukemia (AML) were undertaken, but clinical and immunologic efficacy have proven disappointing. In these studies, the lack of antigen specificity made systematic assessment of the anti-MDS immune response challenging. We hypothesized that combining vaccination against the New York esophageal squamous cell carcinoma 1 (NY-ESO-1) tumor antigen with decitabine and an ICI would allow us to understand antigen-specific immune responses in patients with MDS. To test this hypothesis, we developed an investigator-initiated phase 1 trial in transplant-ineligible patients with MDS/low blast count AML incorporating the anti–programmed cell death protein-1 (PD-1) ICI nivolumab. All patients developed NY-ESO-1–specific CD4+ T-cell responses associated with upregulation of anti–PD-1 immunotherapy gene signatures in the CD4+ T-cell population. Patients had reduced numbers of conventional dendritic cells marked by high expression of CD141 (cDC1), a population critical for successful responses to immunotherapy. cDC1 from patients with MDS showed reduced expression of genes that are key for optimal T-cell activation and expansion. These results suggest that immunotherapy efficacy may vary according to the function of the myeloid immunologic milieu in patients with MDS. Approaches to augment the number and function of cDC1 populations in myeloid disease might overcome this defect and enhance the efficacy of immunotherapy for patients with MDS. This trial was registered at www.ClinicalTrials.gov as #NCT03358719.